Fold-back perineoscrotal flap plus penile inversion vaginoplasty for male-to-female gender reassignment surgery in circumcised subjects - Tavakkoli Tabassi, Kamyar; Djavan, Bob; Hosseini, Jalil; Ghoreifi, Alireza; Ershadi, Mohadese; Hosseini, Elahe (European journal of plastic surgery, 2015)
Background The use of the penile skin for vaginoplasty is a common method in male-to-female (MTF) transsexual surgery. We aim to describe the results of a one-stage vaginoplasty in previously circumcised sex reassignment surgery using fold-back perineoscrotal flap plus penile inversion flap. Methods In a prospective study, 112 previously circumcised MTF subjects underwent a modification of penile inversion vaginoplasty by adding a fold-back perineoscrotal flap to form the whole posterior vaginal wall and about half of the anterior vaginal wall (the proximal part). Patients follow-up, outcomes, and complications were recorded. Results The mean age of the subjects was 25.8 ± 3.3 years underwent feminizing genitoplasty. The success rate was 92.86 %, and the complication-free success rate was achieved in 74.11 % of subjects in general. The need for repeated surgery (failure rate) was 7.14 % (due to vaginal shrinkage in four patients, bulging in anterior vaginal wall in one case and excessive labial skin in three cases). By adding the perineoscrotal flap to the penile skin flap, we were able to reach a mean vaginal depth of 13.1 ± 1.7 and a satisfaction level of 85.71 %. Conclusions Fold-back perineoscrotal flap plus penile inversion vaginoplasty is a suitable surgical approach for achieving adequate vaginal depth in cases of male-to-female (MTF) transsexual vaginoplasty when subjects have short penile skin flap because of circumcision. Level of Evidence: Level III, therapeutic study.